Ligand hydration and bridging waters molecules - Sridhar, A (2016)
Water is the most abundant molecule in biological systems and is ubiquitous in nature. Despite this prevalence, water has long been considered a backdrop for bio-processes. However, with increasing sophistication in experimental and computational methods, water has now been recognized to interact and influence the behaviour of biomolecules in complex, subtle, and essential ways. The structure of water is unique in that it is small yet able to form multiple hydrogen bonded interactions. Water molecules are thus ideally suited to bridge interactions on biomolecular surfaces. Specifically, they have been identified to play an important role in mediating protein-ligand interactions. A methodology for the inclusion of these mediating waters has often been stated to be a major challenge facing the field of rational drug design. While notable successes exist in the design of better binders using water molecules, no single method has been able completely predict the locations of water molecules and its propensity to interact with the binding ligand. This thesis is intended to explore the possibilities of using the hydration of ligands as a pathway to study bridging water molecules in holo structures. To this end, a method of discretizing and scoring water-sites around ligands from their Molecular Dynamics (MD) simulation is first developed. This was then used to correlate the hydration shells of ligands with the locations of the bridging water molecules. Further, the hydration shell of ligands is used to improve WaterDock - a protocol to predict the locations of water molecules within binding sites. Finally, a comparison of MD is made with Empirical Potential Structure Refinement - a combined experimental and computational method that is often used to resolve the solvation structure of small molecules.